العوامل المرتبطة بانتشار عادة التدخين بين طلاب جامعة الأندلس للعلوم الطبية. - جردي, منال (Latakia University Journal -Medical Sciences Series, 2018)
- مقدمة: Background: smoking is a growing public health problem in the world .يعد التدخين السبب الرئيسي للعديد من الأمراض المزمنة وهو مشكلة صحية عامة متنامية في العالم . – الهدف: تهدف هذه الدراسة الى تحديد مدى انتشار عادة التدخين و العوامل المرتبطة among students of Al- Andalus university of medical science . بين طلاب جامعة الأندلس للعلوم الطبية . Methods: A cross sect ional study was conducted - طرق وأدوات البحث: تم إجراء دراسة مقطعية في الفترة الواقعة بين تشرين الاول من العام الدراسي 2017 وحتى شهر أذار من العام الدراسي 2018 وذلك على عينة قوامها 300 طالب في جامعة الأندلس الخاصة للعلوم الطبية حيث استخدمت طريقة العينة الطبقية المنتظمة. Data collected by self-administrated questionnaire.تم جمع البيانات بعد توزيع الاستبيان على طلاب جميع السنوات الدراسية في الكليات الطبية. Results: out of the 300 respondents, 166 students were smokers giving a prevalence rate of 55 %.The prevalence of smokers were much higher in males than females ( 79.5 % and 20.5 %, respectively). - النتائج: من بين 300 مشارك ، كان 166 طالبا مدخنا بمعدل انتشار 55 ٪. كان معدل انتشار المدخنين أعلى بكثير عند الذكور من الإناث ( 79,5 ٪ و 20,5 ٪) على التوالي. 72.2 % of students started smoking at the age of less than 20 years. 72,2 ٪ من الطلاب بدأوا التدخين في عمر يقل عن 20 عامًا، كما بينت النتائج وجود اختلافات ذات دلالة احصائية في التدخين بين الكليات الطبية ( P = 0,02 ) وقد سجلت كلية الطب البشري أعلى نسبة تدخين بين الطلاب. الاستنتاجات والتوصيات: تؤكد هذه الدراسة أن مشكلة التدخين بين طلاب الجامعة ترتبط بالعديد من العوامل الديموغرافية و الشخصية, The study recommends integrating health awareness programmes about smoking hazards in the medical education curriculum.كما توصي هذه الدراسة بأهمية إدخال برامج التوعية الصحية حول مخاطر التدخين في مناهج التعليم الطبي. - Background: smoking is the major cause of many chronic diseases and a growing public health problem in the world. - Aim: the aim of this study is to determine prevalence of smoking habit and associated factors among students of Al-Andalus university of medical science. - Methods: A cross sectional study was conducted from October academic year 2017 to March academic year 2018 on 300 students in Al- andalus Medical University. A systematic stratified sampling method was used. Data collected by self-administrated questionnaire. - Results: out of the 300 respondents, 166 students were smokers giving a prevalence rate of 55%.The prevalence of smokers were much higher in males than females (79.5% and 20.5%, respectively). 72.2% of students started smoking at the age of less than 20 years. There were a significance differences between faculties (P= 0.02) , which faculty of medicine reported high percentage. - Conclusions: This study directs the attention to the fact that problem of smoking among university students has important contributing personal and socio demographic factors. The study recommends integrating health awareness programmes about smoking hazards in the medical education curriculum.